Chemical constituents of Garcinia parvifolia (Guttiferae) - Ee, Gwendoline Cheng Lian; Ng, Sook Han; Goh, Joo Kheng; Md.Sukari, Mohd. Aspollah; Rahmani, Mawardi (University of Malaya, 2009)
Detail chemical studies on Garcinia parvifolia have yielded two triterpenoids, stigmasterol (1) and ?-sitosterol (2), three xanthones, 6-deoxyjacareubin (3), daphnifolin (4) and rubraxanthone (5), one benzophenone, isoxanthochymol (6) and one alkaloid, caffeine (7). These compounds were isolated using common chromatographic techniques and were identified by using spectroscopic experiments such as NMR, MS, IR and UV. This is the first report on the isolation of 6-deoxyjacareubin and daphnifolin from Garcinia parvifolia.